Generalization of certain subclasses of analytic functions - Tadayuki Sekine (International Journal of Mathematics and Mathematical Sciences)
We introduce the subclass Tj(n,m,α) of analytic functions with negative coefficients by the operator Dn. Coefficient inequalities and distortion theorems of functions in Tj(n,m,α) are determind. Further, distortion theorems for fractional calculus of functions in Tj(n,m,α) are obtained.